Radiation Sterilization of Antibiotics in Solid State - Kilińska, Karolina; Zalewski, Przemysław (Current Analytical Chemistry, 2021)
Background: Radiation sterilization is a promising method of obtaining sterile active pharmaceutical ingredients (API), excipients and formulations. One of the best methods of sterilization is to use ionizing radiation. The greatest advantage of ionizing radiation is the fact that it can be conducted at room temperature or lower. Therefore, this procedure of sterilization is reserved for drugs sensitive to the high temperature of autoclaving. Solutions of parenterally administered antibiotics must be absolutely aseptic. Most of the antibiotics are susceptible to degradation at increased temperature and humidity, so radiation is often used to obtain sterile bactericidal drugs. Methods: The available literature and published papers related to radiation sterilization as well as other sterilization methods were collected, analyzed, and reviewed to provide the comprehensive information about the radiation sterilization of antibiotics. The review was critically evaluated and concluded, emphasizing future perspectives for radiation sterilization of antibiotics. Results: The review presented the basic principles, merits, and demerits of radiation sterilization in pharmaceutical samples. Further, the review highlighted the updated summary of the recent advances in terms of the latest regulations and recommendations for radiation sterilization. Conclusion: Radiation sterilization has a promising future in pharmaceutical manufacturing processes. This approach is compatible with various types of material, is easy to control, does not increase the temperature of the process, and from the business point of view - can help to save money and time during manufacturing solid dosage forms of medicines. From the pharmaceutical sense, fully effective sterilization in the terminal step - finished packed product - is the most important advantage of radiation sterilization.
Keywords: tertracyclines